RELATIONSHIP OF SUBJECT PREPARATION AND MOTIVATION OF STUDENTS IN THE PROCESS OF PROFESSIONAL SELF-ORIENTATION - Papoyan, V.R.; Galstyan , A. S.; Sargsyan , D. Yu. (Modern Psychology, 2019)
The article is dedicated to the psychological assessment of students' professional self-orientation, the purpose of which is to study the correlation between their own knowledge, desires and professional relevance. The article summarizes the results of 395 the study showing that the surveyed respondents (70 people) are highly motivated, independent and their life decisions are specific. However, their concepts of choosing a profession are weak due to their knowledge, faithful desires and preferences. It was obvious that many of the students who were on the threshold of choosing a profession had no idea about the professions. The data obtained allow us to conclude that students do not get efficient awareness of professions at the relevant stages of training, this, in its turn makes the choice and professional self-orientation difficult.
Keywords: student, professional self-orientation, motivation, preference.